Design of novel triply periodic minimal surface (TPMS) bone scaffold with multi-functional pores: lower stress shielding and higher mass transport capacity - Jiang, Jian; Huo, Yi; Peng, Xing; Wu, Chengwei; Zhu, Hanxing; Lyu, Yongtao (Frontiers in Bioengineering and Biotechnology, 2024)
The design of bone scaffolds is a complex process, as the scaffolds must satisfy various clinical requirements, including appropriate mechanical properties and sufficient mass transport capacity. Novel triply periodic minimal surface (TPMS)-based bone scaffolds were designed in this study to improve the mechanical and biological performances simultaneously. The novel bone scaffolds were designed by adding optimization-guided multi-functional pores to the original scaffolds, and both finite element (FE) method and experimental method were used to evaluate the performances of the novel bone scaffolds. The FE results demonstrated the improvement in performance: the elastic modulus reduced from 5.58 GPa (original scaffold) to 3.38 GPa (novel designed scaffold), resulting in lower stress shielding; the permeability increased from 8.58 × 10 -9 m 2 (original scaffold) to 5.14 × 10 -8 m 2 (novel designed scaffold), resulting in higher mass transport capacity. In summary, the novel TPMS scaffolds with multi-functional pores simultaneously improve the mechanical and biological performances, making them ideal candidates for bone repair. Furthermore, the novel scaffolds expanded the design domain of TPMS-based bone scaffolds, providing a promising new method for the design of high-performance bone scaffolds.